Effect of Al anodizing waste on the final properties of porous geopolymers. (10th December 2020) - Buruberri, L.H.; Senff, L.; Seabra, M.P.; Labrincha, J.A.
Graphical abstract: Highlights: Al-anodizing sludge as an agent to control the porous architecture of geopolymers. Development of bodies with high total (≈ 85%) and open (≈ 70%) porosity values. Were developed geopolimeric materials with low thermal conductivity and water vapour diffusion resistance. Abstract: The Achilles heel in the production of porous geopolymers (PGPs) by the direct foaming technique is the porous coalescence phenomenon. The control of pore size distribution and porosity type (closed or open) is mandatory, although difficult. In most of the published studies, this problem is overcome through the addition of chemical stabilizing agents (surfactants) or thickening agents (fibers or particles). In this work, porous geopolymers were produced by the direct foaming technique using aluminium powder as a chemical foaming agent. The pore size distribution and porosity type was controlled by adding, to the geopolymeric mixture, Al-anodising sludge (AAS), a waste resulting from aluminium surface treatment. The PGPs were characterized in terms of apparent density, porosity, pore morphology, thermal conductivity, water vapour permeability and compressive strength, yielding lightweight materials (0.339 g/cm 3 ) exhibiting high total (84%) and open (70%) porosity, low thermal conductivity (0.082 W/mK) and a low water vapour diffusion resistance coefficient. Compressive strength (of about 2 MPa or higher) is enough for the applications ( e.g. insulating materials, filters, lightweight structures).